Frequency Interpretation of Probability - Nekrašas, Evaldas (Problemos, 1971)
Some difficulties in frequency interpretation of probability as formulated in the object - language are analysed in the paper. Existence and uniqueness aspects of the limits of relative frequencies in the empirical series of events are investigated and the problem of separate event probability in the frequency theory of probabilities is discussed. The problem is not a theoretical but a practical one, since theoretically it is soluble when a separate event is taken to represent some class. The referent class establishing procedure and expediency of class con traction are considered. The author asserts in this respect that frequency interpretation has more advantages over other conceptions of probability. On the other hand, the possibility of fixing the limit of relative frequencies in the empirical series is questioned.